2022
DOI: 10.3390/cancers14123009
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Biological and Physical Basis of Boron Neutron Capture Therapy (BNCT) as a Promising Treatment Frontier in Breast Cancer

Abstract: BNCT is a high LET radiation therapy modality that allows for biologically targeted radiation delivery to tumors while reducing normal tissue impacts. Although the clinical use of BNCT has largely been limited to phase I/II trials and has primarily focused on difficult-to-treat malignancies such as recurrent head and neck cancer and recurrent gliomas, recently there has been a renewed interest in expanding the use of BNCT to other disease sites, including breast cancer. Given its high LET characteristics, its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 58 publications
0
25
0
Order By: Relevance
“…The basic idea in the nIORT® is to irradiate tumour beds "directly" with the monoenergetic 2.45 MeV neutrons emitted by the DD source, e.g., without moderating to epithermal or thermal energies as in the BNCT. 5,6,7 This high energy neutrons are very effective in cancer cells killing because of their high LET and RBE: @16 for 2.45 MeV neutrons. 9,30 This RBE value is significantly higher than of the proton in the Spread Out Bragg Peak (SOBP, estimated to be 1.1 to 1.2) and of the currently used 50 kV Xrays medical devices for IORT, which are 1.26 to 1.42 as measured in a phantom model.…”
Section: Background Research Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The basic idea in the nIORT® is to irradiate tumour beds "directly" with the monoenergetic 2.45 MeV neutrons emitted by the DD source, e.g., without moderating to epithermal or thermal energies as in the BNCT. 5,6,7 This high energy neutrons are very effective in cancer cells killing because of their high LET and RBE: @16 for 2.45 MeV neutrons. 9,30 This RBE value is significantly higher than of the proton in the Spread Out Bragg Peak (SOBP, estimated to be 1.1 to 1.2) and of the currently used 50 kV Xrays medical devices for IORT, which are 1.26 to 1.42 as measured in a phantom model.…”
Section: Background Research Studiesmentioning
confidence: 99%
“…Indeed, the almost spherically symmetric IR on the tumour bed has the advantages to be less sensitive to the margins of the surgery cavity and to the possible intra-tumour heterogeneity of the solid tumour cells since the neutron irradiator behaves like an IR "foam" within the cavity. Differently from the Boron Neutron Capture Therapy (BNCT) exploiting thermal and epithermal neutrons to induce (n, a) reactions in boron carriers injected into patients 5,6,7 , the fast neutrons interact directly and efficiently with the hydrogen nuclei, producing recoil protons that ionize the tissues. Monte Carlo simulations have shown that the nIORT® delivers on the tumour bed a fast-neutron IR with a high linear energy transfer (LET) 8 and a relative biological effectiveness (RBE) 9 significantly higher than all other IRs such as X-rays, electrons and protons, thus resulting very efficient in producing DNA double strand breaks (DSBs) of the cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…Of the boron-containing agents reported so far, boronophenylalanine (BPA) and borocaptate sodium (BSH) are the two most commonly used boron agents for clinical treatment ( Figure 1 ). In addition, various boron agents have been developed in the past decades, including peptides [ 27 , 28 ], antibody-based delivery systems [ 29 , 30 ], boron compound conjugates [ 31 , 32 ], boron-containing nanoparticles [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ], boric acid [ 41 , 42 , 43 ], and decahydrodecaborate (GB-10) [ 44 , 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is a binary treatment that combines the administration of boron-10 carriers that are taken up preferentially by tumor cells and the subsequent irradiation with a thermal/epithermal neutron beam. The nuclear reaction between a 10 B atom (a stable isotope) and a thermal neutron generates high linear energy transfer (LET) particles (alpha particles and 7 Li recoil nuclei) and low LET gamma radiation [1][2][3]. High LET particles travel a short distance in tissue, approximately the diameter of a single tumor cell (10 µm); thus, they only destroy 10 B-containing tumor cells [4], preserving the surrounding normal tissue.…”
Section: Introductionmentioning
confidence: 99%
“…BNCT clinical trials on recurrent glioblastoma, primary and recurrent head and neck cancer, sarcoma, meningioma, melanoma, hepatocellular carcinoma, and malignant mesothelioma were and/or are currently performed around the world [6,7]. Particularly, for the treatment of recurrent head and neck tumors, the BNCT overall tumor response rate was up to 90% [2].…”
Section: Introductionmentioning
confidence: 99%